Ni-based'bimetallic-alkali-acid 'multifunctional hydrotalcite catalyst as well as preparation method and application thereof
By using the Ni-based "bimetal-alkali-acid" multifunctional hydrotalcite catalyst, the synergistic effect of Ni-N bimetal and alkali acid sites was used to solve the problems of insufficient vitality and poor stability of existing catalysts, and the efficient semi-hydrogenation conversion of dimethyl maleate and the high selective preparation of dimethyl succinate were achieved.
Patent Information
- Application Number
- CN202411904835.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Ni hydrotalcite catalysts have problems such as insufficient vitality, easy aggregation or loss of metal particles, and poor circulation stability in the semi-hydrogenation reaction of dimethyl maleate, resulting in low production efficiency and high cost.
The Ni-based "bimetallic-alkali-acid" multifunctional hydrotalcite catalyst is used. This catalyst is prepared by synthesizing Ni-N-MO-Al hydrotalcite precursor oxide with a layered porous structure and is prepared by efficient in situ desolution method. The Ni-N bimetallic hydrogenation active site, MO alkaline site and Lewis acid site of the Al framework are used to achieve highly selective preparation of dimethyl succinate.
The long-term stability and high-definition of the catalyst are achieved, production costs are reduced, reaction efficiency is improved, and there are almost no by-products. The conversion rate of dimethyl maleate and dimethyl succinate are both reached 100%.
Smart Images

Figure CN119701967A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic synthesis of fine chemicals, and specifically relates to a Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst and a preparation method and application thereof. Background Art
[0002] In today's world, plastic products have brought many conveniences to people's lives. At the same time, a large amount of discarded plastics has also caused serious pollution to the environment. The development of biodegradable plastics is of great significance to solving problems such as "white pollution", oil depletion, and global warming, and is more in line with the concept of sustainable development. Dimethyl succinate (DMS) can be used as a key raw material for biodegradable plastic polybutylene succinate (PBS), and the domestic market is currently extremely vacant. The traditional industrial synthesis of DMS is mainly obtained by esterification reaction using succinic acid and methanol as raw materials and concentrated sulfuric acid as a catalyst. However, this process of esterification catalyzed by concentrated sulfuric acid has many side reactions, low yield, complex post-processing, and serious equipment corrosion. The by-product is highly toxic dimethyl sulfate, which seriously pollutes the environment. The latest process of dimethyl succinate is obtained by partial hydrogenation reaction using dimethyl maleate (DMM) and hydrogen as raw materials using Ni catalyst.
[0003] For example, Chinese patent CN103657693A discloses a dimethyl maleate hydrogenation catalyst, which uses nickel hydrotalcite as a carrier, is prepared by loading Pd and then loading the remaining trace elements, and the preparation process of the catalyst is complicated, the cost is relatively high, and the catalyst is weak in interaction between the metal and the carrier, and the Ni activity is insufficient during high-temperature reduction and liquid-phase hydrogenation, and the metal particles are easily aggregated or lost, and the large-particle metal Ni site is easily deactivated by carbon deposition, resulting in poor catalyst cycle stability. Frequent catalyst replacement will affect production efficiency and increase production costs. Summary of the invention
[0004] In view of the technical problems existing in the semi-hydrogenation reaction of dimethyl maleate by the above Ni-based hydrotalcite catalyst, the purpose of the present invention is to provide a Ni-based "bimetallic-alkali-acid" multifunctional hydrotalcite catalyst which is cheap, simple to prepare, can catalyze the semi-hydrogenation of dimethyl maleate to dimethyl succinate with high specificity and long-term stability, as well as a preparation method and application. The present invention first synthesizes a Ni-N-MO-Al hydrotalcite precursor oxide with a layered porous structure (the main metal is Ni, the second metal N is one of Cr, Mn, Fe, Co or Cu, and M in the alkali metal oxide MO is one of Mg, Ca, Sr, Ba, Cd and Zn), and then prepares the Ni-based "bimetallic-alkali-acid" multifunctional hydrotalcite catalyst by an efficient in-situ precipitation method. The present invention makes full use of the multi-center synergistic effect of the catalyst, including the Ni-N bimetallic hydrogenation active site, the MO basic site and the Lewis acidic site of the Al skeleton, and realizes the highly selective preparation of the target product dimethyl succinate under mild conditions through the bimetallic-base-acid multi-site synergistic catalytic effect and the strong metal-carrier interaction.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] On the one hand, the present invention provides a Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst. The general formula of the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst is Ni-N-MO-Al2O3, wherein N represents one of Cr, Mn, Fe, Co or Cu, and MO represents an oxide of Mg, Ca, Sr, Ba, Cd or Zn; the catalyst uses Al2O3 as a carrier, Ni, N and MO as metal active components, the carrier Al2O3 maintains a partial lamellar skeleton structure of the hydrotalcite at the nanoscale, and nanoparticles of the metal active components Ni and N and MO are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, Ni-N alloy nanoparticles and MO are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
[0007] Furthermore, in terms of mass percentage, the contents of the components in the Ni-N-MO-Al2O3 are as follows: Ni is 20-35%, N is 10-20%, MO is 8-35%, and Al2O3 is 35-55%.
[0008] Furthermore, the specific surface area of Ni-N-MO-Al2O3 is 145 to 180 m 2 ·g -1 The average pore size is 5-13 nm and the pore volume is 0.30-0.60 cm 3 ·g -1 , the Ni-N alloy particle size is 3.6~7.5nm.
[0009] Another aspect of the present invention provides a method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst as described above, comprising the following steps:
[0010] (1) dissolving nickel salt, N salt, M salt and aluminum salt in deionized water to prepare a metal salt solution; dissolving NaOH in deionized water to prepare a NaOH solution; dissolving Na2CO3 in deionized water to prepare a Na2CO3 solution;
[0011] (2) dropping the metal salt solution and the NaOH solution into the Na2CO3 solution simultaneously for precipitation titration;
[0012] (3) aging the precipitation solution after the precipitation is completed to obtain a precursor precipitate;
[0013] (4) The precursor precipitate is washed, dried, and activated to obtain the catalyst Ni-N-MO-Al2O3.
[0014] Furthermore, in step (1), the nickel salt, N salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, N salt, M salt and aluminum salt is 1-2:0.5-1:0.5-1:1, and the molar fraction ratio of the nickel salt + N salt + M salt and aluminum salt is 2-4:1.
[0015] Furthermore, in the step (1), the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume is 75-250 mL; the concentration of the NaOH solution is 1-1.8 mol / L, and the volume is 150-200 mL; the concentration of the Na2CO3 solution is 0.3-0.6 mol / L, and the volume is 150-200 mL.
[0016] Furthermore, in the precipitation titration process in step (2), the volume flow ratio of the metal salt solution and the NaOH solution is controlled to be 0.75-2.5:1.5-2, the titration rate is 0.5-2.5 mL / min, the pH value of the mixed solution is maintained at 9-11, and the operating temperature is 50-100° C.; in step (3), the aging temperature is 20-30° C., and the aging time is 12-36 hours.
[0017] Furthermore, the washing liquid used in step (4) is deionized water, ethanol or a mixed solution of ethanol / water with a volume ratio of 3:1 to 1:3, and the number of washings is 3 to 5 times; the drying temperature is 70 to 200° C., and the drying time is 8 h to 20 h.
[0018] Furthermore, the activation treatment in step (4) includes: activation treatment 1: first calcining at 350°C to 600°C for 3h to 6h in a static air, flowing air, static nitrogen or flowing nitrogen atmosphere, with a heating rate of 2°C / min to 10°C / min; then reducing at 400°C to 600°C for 3h to 5h in a flowing hydrogen or hydrogen / nitrogen mixed gas atmosphere with a volume ratio of 1:0 to 3, with a heating rate of 2°C / min to 10°C / min; or activation treatment 2: directly reducing at 400°C to 600°C for 3h to 5h in a flowing hydrogen or hydrogen / nitrogen mixed gas atmosphere with a volume ratio of 1:0 to 3, with a heating rate of 2°C / min to 10°C / min.
[0019] Another aspect of the present invention provides the use of the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst as described above for semi-hydrogenation of dimethyl maleate to prepare dimethyl succinate.
[0020] The Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst of the present invention is mainly used for the semi-hydrogenation reaction of dimethyl maleate, and the specific evaluation method is: the catalyst activity is examined in a 100mL stainless steel high-pressure hydrogenation reactor. In the experiment, 3-15mL dimethyl maleate, 20-60 mesh 0.06-0.3g Ni-N-MO-Al2O3 catalyst and 0-70mL anhydrous methanol or deionized water solvent are loaded into the high-pressure reactor. After sealing, the reaction system is first flushed with N2 and H2 for 5 times each, and then pressurized to the required pressure with pure H2. The reaction temperature and pressure are set at 50-250℃ and 1-5MPa, and the reaction is continued for 20min-3h at a stirring rate of 200-600r / min. The product after the reaction was analyzed by gas chromatography (Aglient 7890A), and the contents of the components in the liquid and gas phases were detected by hydrogen ion flame detector (FID) and TCD. The capillary column was HP-5 and the filling column was TDX-1.
[0021] In the process of hydrogenating dimethyl maleate to dimethyl succinate, mixed hydrogenation of various functional groups such as C=C, C=O, -CO-OR is involved, including hydrogenation reaction of polyesters, hydrogenation reaction of lactones, intramolecular dehydration reaction, etc., and there is an inhibitory effect of chemical equilibrium. Especially under high temperature and high pressure, -COO- and C=O are more easily activated, and the reaction rate of hydrogenation to produce other by-products will be accelerated. In addition to dimethyl succinate (DMS), the product system also has by-products such as γ-butyrolactone (GBL), 1,4-butanediol (BDO) and tetrahydrofuran (THF). Therefore, in order to achieve complete conversion of dimethyl maleate and high selectivity of dimethyl succinate, it is required that the catalyst used can activate C=C and inhibit C=O hydrogenation and -COO- hydrogenolysis. The hydrogenation process of dimethyl maleate is complex and belongs to a multi-step cascade reaction. In addition to dimethyl succinate (DMS), the product system also contains byproducts such as γ-butyrolactone (GBL), 1,4-butanediol (BDO) and tetrahydrofuran (THF). The hydrogenation process involves the mixed hydrogenation of multiple functional groups such as C=C, C=O, -CO-OR, including polyester hydrogenation reaction, lactone hydrogenation reaction, intramolecular dehydration reaction, etc., and there is an inhibitory effect of chemical equilibrium. Especially under high temperature and pressure, -COO- and C=O are more easily activated, and the reaction rate of hydrogenation to produce other byproducts will be accelerated. Therefore, in order to achieve the complete conversion of dimethyl maleate and the high selectivity of dimethyl succinate, it is required that the catalyst used can not only activate C=C, but also inhibit C=O hydrogenation and -COO- hydrogenolysis. The Ni-N-MO-Al2O3 metal-base-acid multifunctional hydrotalcite catalyst of the present invention is a supported metal catalyst prepared by a structural topological transformation process of a layered double hydroxide (LDHs) precursor, and its "surface trap structure" and "surface mesh structure" can provide anchoring points for active components, thereby improving the dispersion and stability of active components on the catalyst surface. The design idea of the present invention is to provide a Ni-N-MO-Al2O3 quaternary catalyst, which is composed of active components Ni, N (one of Fe, Co, Cu, Cr, Mn), MO (one of Mg, Ca, Sr, Ba, Cd, Zn oxide) and Al2O3, and has a more regular pore distribution and a larger specific surface area than the supported nickel-based catalyst prepared by the traditional method, and is easier to adjust the metal-support interaction (for example, electronic metal-support interaction, metal / support acid-base interaction). First, after the introduction of the second metal N, the alloying of Ni and N reduces the d-band center of Ni, which is beneficial to the desorption of H*. N can form an electronic effect with the active metal Ni, weakening the electron density of Ni after reduction, which is beneficial to the reduction of Ni, reducing the reduction temperature of the active component oxide, and improving the low-temperature activity of the catalyst. The Ni-N synergistic bimetallic effect rapidly hydrogenates the reaction substrate from C=C to CC. Secondly, the Lewis acid sites (Al3+ ) adsorbs and polarizes the oxygen atom on the ester group (*O=C) by p-π conjugation effect, and at the same time, the strong basic position (*M 2+ -O 2- The π* acceptor orbital on the ester group (O=CO*) is easy to interact with the π* acceptor orbital on the carbon atom, thereby promoting the adsorption and occupation of the C=O / CO bond in the DMM molecule and inhibiting its further hydrogenation. Therefore, this quaternary synergistic catalytic effect between the Ni-N bimetallic and the base-acid center and the strong metal carrier base-acid interaction are conducive to the activation adsorption of DMM and the subsequent hydrogenation reaction, so that the catalyst shows excellent low-temperature activity, high high-temperature specificity and selectivity in the dimethyl maleate reaction after reduction activation. Dimethyl maleate can be almost completely converted at a higher feedstock space velocity, and a higher selectivity for dimethyl succinate is obtained, with almost no by-products. For example, under the conditions of a reaction temperature of 50 to 250°C and a reaction pressure of 1 to 5MPa, the conversion rate of dimethyl maleate can reach 100%, and the selectivity of dimethyl succinate is 100%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst of the present invention has a long service life, a simple preparation process, a low cost, a strong metal-carrier interaction, a uniform distribution of the active phase, a high degree of dispersion, and the active metal sites are not easy to migrate or lose under high temperature or liquid phase conditions.
[0024] 2) The various N elements or M elements introduced in the present invention have either close atomic radii or similar crystallization chemical potentials to the Ni / Al elements, and are very easy to eutectically grow into a hydrotalcite layer microstructure with uniformly arranged Ni-NM-Al atoms during the precipitation process, which is one of the prerequisites for ensuring that the catalyst has a bimetallic-base-acid multifunctional synergistic effect after reduction activation.
[0025] 3) The present invention prepares Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst by an efficient in-situ desolvation method. After reduction, the active metals Ni and N are dissolved from the skeleton structure to the catalyst surface to form a Ni-N alloy. The metals have a strong synergistic effect. The presence of N species increases the adsorption of active H species on the catalyst surface. The bimetallic synergistic effect promotes the active metal Ni 0 The site rapidly hydrogenates the reaction from C=C to CC, and the Lewis acid sites (Al 3+ ) adsorbs and polarizes the oxygen atom on the ester group (*O=C), while the medium-strong alkaline position (*M 2+ -O 2-The two together inhibit the adsorption between the ester group (O=C) and the active component, effectively reducing the loss of active components. The four bimetallic base and acid sites work together to effectively improve the hydrogenation activity of the catalyst and extend the service life of the catalyst.
[0026] 4) The Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst of the present invention has a low activation temperature, good low-temperature activity, and high high-temperature specificity in the hydrogenation reaction. The preferred low-temperature reaction conditions (50-100°C) can effectively inhibit the high-temperature polymerization of C4 unsaturated substances in the raw materials during the hydrogenation reaction. At the same time, the addition of the alkaline additive reduces the acidity of the catalyst surface, enhances the interaction between the metal active component and the carrier, and increases the dispersion of the active metal. The alkaline site can effectively inhibit the nucleation and accumulation of carbon deposit intermediates under high-temperature reaction conditions, avoiding the risk of metal sites being covered by oligomers and carbon deposits, and ensuring the long-term reaction stability of the catalyst.
[0027] 5) In the preparation method of the present invention, the trivalent cations on the LDHs layer plate make the layer plate skeleton positively charged, and the anions with opposite charges between the layers balance it, making the entire crystal electrically neutral. The divalent metal ions and trivalent metal ions with hydrogenation activity are introduced into the LDHs layer plate. Under the combined influence of the lowest lattice energy and the positioning effect of atoms in the crystal, these metal active components are highly dispersed in the LDHs precursor, and the introduction of the second metal N can form an electronic effect with the active metal, and can effectively control the size of Ni particles, inhibit the migration and agglomeration of Ni nanoparticles, greatly reduce the reduction temperature of the active component oxide, and improve the low-temperature activity and stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a working principle diagram of the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst of the present invention;
[0029] Figure 2 It is the X-ray diffraction spectra of the sample after calcination of the precursor of catalyst 1 of the present invention, the sample after H2 activation and the sample after H2 activation of comparative catalyst 1;
[0030] Figure 3 The N2 adsorption-desorption curve (left) and pore size distribution (right) of the catalyst 5 of the present invention after calcination;
[0031] Figure 4 It is the H2-programmed temperature reduction diagram of comparative catalyst 1 and catalyst 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Preparation Example 1
[0034] 1) Weigh 7.3 g of nickel nitrate hexahydrate, 3.7 g of cobalt nitrate hexahydrate, 3.2 g of magnesium nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 150 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.5 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt, magnesium salt and aluminum salt is 1:0.5:0.5:1); weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (the concentration is 1 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.3 mol / L), stir at a speed of 800 r / min, and stir evenly for 1 h.
[0035] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 50°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 2mL / min, with a stirring rate of 800r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.5:2, and maintain the pH value of the mixed solution at 9. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 24h at a stirring rate of 550r / min to obtain a precursor precipitate.
[0036] 3) The precursor precipitate was repeatedly washed with deionized water for 6 times until neutral, placed in an oven at 100°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 350°C in static air for 6 hours at a heating rate of 0.5°C / min, cooled to room temperature, and then introduced into a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:3, and the temperature was raised from room temperature to 550°C for 3 hours for reduction, and then taken out after cooling to room temperature to obtain catalyst 1. The active metal content and texture and structural parameters of catalyst 1 are shown in Table 1.
[0037] Preparation Example 2
[0038] 1) Weigh 5.5 g of nickel nitrate hexahydrate, 7.5 g of chromium nitrate nonahydrate, 4.8 g of magnesium nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate and dissolve them in 200 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.375 mol / L, and the molar fraction ratio of the nickel salt, chromium salt, magnesium salt and aluminum salt is 1:1:1:1); weigh an appropriate amount of NaOH and dissolve it in 150 mL of deionized water to prepare a NaOH solution (the concentration is 1 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.3 mol / L), stir them at a speed of 500 r / min, and stir evenly for 40 min.
[0039] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 75°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 0.9mL / min, with a stirring rate of 600r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 2:1.5, and maintain the pH value of the mixed solution at 11. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 36 hours at a stirring rate of 500r / min to obtain a precursor precipitate.
[0040] 3) The precursor precipitate was repeatedly washed with deionized water for 5 times until neutral, placed in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 500°C for 4 hours in static air at a heating rate of 8°C / min, cooled to room temperature, and then introduced into a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:2, and then heated from room temperature to 600°C for 3 hours. After cooling to room temperature, it was taken out to obtain catalyst 2. The active metal content and texture and structural parameters of catalyst 2 are shown in Table 1.
[0041] Preparation Example 3
[0042] 1) Weigh 8.7 g of nickel nitrate hexahydrate, 6.1 g of ferric nitrate nonahydrate, 3.8 g of magnesium nitrate hexahydrate and 5.6 g of aluminum nitrate nonahydrate and dissolve them in 250 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.3 mol / L, and the molar fraction ratio of the nickel salt, iron salt, magnesium salt and aluminum salt is 2:1:1:1); weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (the concentration is 1.8 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.6 mol / L), stir them at a speed of 600 r / min, and stir evenly for 30 min.
[0043] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 75°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 2.5mL / min, with a stirring rate of 540r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 2.5:2, and maintain the pH value of the mixed solution at 10. After the crystallization is completed, the precipitation solution is cooled to 20°C and aged for 12 hours at a stirring rate of 660r / min to obtain a precursor precipitate.
[0044] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 70°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 450°C in static air for 5 hours at a heating rate of 1°C / min, cooled to room temperature, and then introduced with a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:1, and then heated from room temperature to 550°C for 3 hours for reduction, cooled to room temperature and taken out to obtain catalyst 3. The active metal content and texture and structural parameters of catalyst 3 are shown in Table 1.
[0045] Preparation Example 4
[0046] 1) Weigh 7.3 g nickel nitrate hexahydrate, 3.0 g copper nitrate trihydrate, 3.0 g calcium nitrate tetrahydrate and 9.4 g aluminum nitrate nonahydrate and dissolve them in 190 mL deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.4 mol / L, and the molar fraction ratio of the nickel salt, copper salt, calcium salt and aluminum salt is 1:0.5:0.5:1); weigh an appropriate amount of NaOH and dissolve it in 150 mL deionized water to prepare a NaOH solution (the concentration is 1.3 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL deionized water to prepare a Na2CO3 solution (the concentration is 0.5 mol / L), stir at a speed of 500 r / min, and stir evenly for 2 h.
[0047] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 95°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 0.8mL / min, with a stirring rate of 600r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.9:1.5, and maintain the pH value of the mixed solution at 11. After the crystallization is completed, the precipitation solution is cooled to 20°C and aged for 24h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0048] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 500°C for 4 hours in static air at a heating rate of 8°C / min, cooled to room temperature, introduced with hydrogen reduction gas, and then heated from room temperature to 600°C for 3 hours, cooled to room temperature and taken out to obtain catalyst 4. The active metal content and texture and structural parameters of catalyst 4 are shown in Table 1.
[0049] Preparation Example 5
[0050] 1) Weigh 5.5 g of nickel nitrate hexahydrate, 5.4 g of manganese nitrate hexahydrate, 5.6 g of zinc nitrate hexahydrate and 7.2 g of aluminum nitrate nonahydrate and dissolve them in 100 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.75 mol / L, and the molar fraction ratio of the nickel salt, manganese salt, zinc salt and aluminum salt is 1:1:1:1); weigh an appropriate amount of NaOH and dissolve it in 150 mL of deionized water to prepare a NaOH solution (the concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.45 mol / L), stir them at a speed of 600 r / min, and stir evenly for 4 h.
[0051] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 0.8mL / min, with a stirring rate of 540r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 1:1.5, and maintain the pH value of the mixed solution at 10. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 12 hours at a stirring rate of 800r / min to obtain a precursor precipitate.
[0052] 3) The precursor precipitate was repeatedly washed with deionized water for 6 times until neutral, placed in an oven at 100°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 450°C for 4 hours in static air at a heating rate of 2°C / min, cooled to room temperature, and then introduced with a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:2.5, and then heated from room temperature to 550°C for 3 hours for reduction, cooled to room temperature and taken out to obtain Catalyst 5. The active metal content and texture and structural parameters of Catalyst 5 are shown in Table 1.
[0053] Preparation Example 6
[0054] 1) Weigh 8.7 g of nickel nitrate hexahydrate, 4.4 g of cobalt nitrate hexahydrate, 3.9 g of barium nitrate and 5.6 g of aluminum nitrate nonahydrate and dissolve them in 115 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.65 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt, barium salt and aluminum salt is 2:1:1:1); weigh an appropriate amount of NaOH and dissolve it in 170 mL of deionized water to prepare a NaOH solution (the concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 170 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.45 mol / L), stir at a speed of 550 r / min, and stir evenly for 3 h.
[0055] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 1.78mL / min, with a stirring rate of 560r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.15:1.7, and maintain the pH value of the mixed solution at 10. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 36 hours at a stirring rate of 660r / min to obtain a precursor precipitate.
[0056] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until neutral, placed in an oven at 95°C for 12 hours, moved to a tube furnace for activation treatment, calcined at 480°C in static air for 4 hours at a heating rate of 5°C / min, cooled to room temperature, and then introduced with a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:.5, and then heated from room temperature to 400°C for reduction for 5 hours, cooled to room temperature and taken out to obtain Catalyst 6. The active metal content and texture and structural parameters of Catalyst 6 are shown in Table 1.
[0057] Preparation Example 7
[0058] 1) Weigh 7.3 g nickel nitrate hexahydrate, 3.7 g cobalt nitrate hexahydrate, 3.9 g cadmium nitrate tetrahydrate and 9.4 g aluminum nitrate nonahydrate and dissolve them in 125 mL deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 0.6 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt, cadmium salt and aluminum salt is 1:0.5:0.5:1); weigh an appropriate amount of NaOH and dissolve it in 150 mL deionized water to prepare a NaOH solution (the concentration is 1.5 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 150 mL deionized water to prepare a Na2CO3 solution (the concentration is 0.45 mol / L), stir at a speed of 500 r / min, and stir evenly for 2.5 h.
[0059] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 0.5mL / min, with a stirring rate of 600r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 1.25:1.5, and maintain the pH value of the mixed solution at 11. After the crystallization is completed, the precipitation solution is cooled to 25°C and aged for 24h at a stirring rate of 660r / min to obtain a precursor precipitate.
[0060] 3) The precursor precipitate was repeatedly washed with deionized water for 5 times until it was neutral, placed in an oven at 90°C for 12 hours, moved to a tube furnace for activation treatment, and then hydrogen reduction gas was introduced, and then the temperature was raised from room temperature to 600°C for reduction for 4 hours, and then taken out after cooling to room temperature to obtain catalyst 7. The active metal content and texture and structural parameters of catalyst 7 are shown in Table 1.
[0061] Preparation Example 8
[0062] 1) Weigh 5.5 g of nickel nitrate hexahydrate, 7.5 g of chromium nitrate nonahydrate, 4.0 g of strontium nitrate and 7.2 g of aluminum nitrate nonahydrate and dissolve them in 75 mL of deionized water to prepare a metal salt solution (the total concentration of the metal salt solution is 1 mol / L, and the molar fraction ratio of nickel salt, chromium salt, strontium salt and aluminum salt is 1:1:1:1); weigh an appropriate amount of NaOH and dissolve it in 200 mL of deionized water to prepare a NaOH solution (the concentration is 1.3 mol / L); weigh an appropriate amount of Na2CO3 and dissolve it in 200 mL of deionized water to prepare a Na2CO3 solution (the concentration is 0.5 mol / L), stir at a speed of 500 r / min, and stir evenly for 6 h.
[0063] 2) Place the prepared Na2CO3 solution in a 1L beaker, raise the operating temperature to 65°C, then place the prepared metal salt solution and NaOH solution in burettes respectively, and titrate them into the Na2CO3 solution at a titration rate of 0.6mL / min, with a stirring rate of 500r / min, and control the volume flow ratio of the metal salt solution and the NaOH solution to be 0.75:2, and maintain the pH value of the mixed solution at 9. After the crystallization is completed, the precipitation solution is cooled to 30°C and aged for 36 hours at a stirring rate of 660r / min to obtain a precursor precipitate.
[0064] 3) The precursor precipitate was repeatedly washed with deionized water for 4 times until it was neutral, placed in an oven at 200°C for 12 hours, moved to a tube furnace for activation treatment, and then introduced a hydrogen / nitrogen reducing gas with a volume flow ratio of 1:3, and then heated from room temperature to 400°C for reduction for 5 hours, and then taken out after cooling to room temperature to obtain Catalyst 8. The active metal content and texture and structural parameters of Catalyst 8 are shown in Table 1.
[0065] Preparation Comparative Example 1
[0066] 4) Without adding the second metal element, only 14.5 g of nickel nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate were weighed, and the other preparation steps were the same as those in Example 1 to obtain Comparative Catalyst 1. The active metal content and texture and structural parameters of Comparative Catalyst 1 are shown in Table 1.
[0067] Table 1 Active metal content and texture and structural parameters of catalysts 1 to 8 and comparative catalyst 1
[0068]
[0069] Characterization Test
[0070] (1) XRD characterization
[0071] Figure 2 It is the X-ray diffraction spectrum of the sample after calcination of the precursor of catalyst 1 of the present invention, the sample after H2 activation, and the sample of comparative catalyst 1 after H2 activation. It can be seen from the figure that after the catalyst 1 of the present invention is calcined at 350°C, the collapse of its layered structure causes the characteristic diffraction peak of LDH to disappear, and the interlayer anions are removed to form a mixed metal oxide phase of MgO-NiO periclase and Co2AlO4 spinel. After H2 activation, the diffraction peak of the hydrotalcite of comparative catalyst 1 disappears, and characteristic diffraction peaks appear at 44.3°, 51.9°, and 76.8°. These diffraction peaks correspond to the (111), (200), and (220) crystal planes of Ni. In catalyst 1, new Ni x Co y This is because the addition of Co species will cause defect sites in metallic Ni, resulting in the formation of a uniform Ni-Co metal alloy inside or on the inner surface of the Al2O3 framework.
[0072] (2) BET characterization
[0073] Figure 3 The N2 adsorption-desorption curve (left) and pore size distribution (right) of the catalyst 5 of the present invention after calcination. It can be seen from the figure that the catalyst 5 of the present invention presents a typical IV type isotherm and has an obvious hysteresis loop, indicating that a good mesoporous structure is formed during the calcination process; from the pore size distribution diagram, it can be seen that the pore size distribution is around 5nm.
[0074] (3) H2 temperature-programmed reduction characterization
[0075] Figure 4It is the H2-programmed temperature reduction diagram of comparative catalyst 1 and catalyst 1 of the present invention. Comparative catalyst 1 has two obvious H2 reduction signal peaks, and the corresponding central temperatures are 325°C and 500°C, respectively. The reduction peak at low temperature (325°C) comes from the reduction of the Ni component with weak interaction with the carrier, while the reduction peak at high temperature (500°C) corresponds to the reduction of the Ni component with strong interaction with the carrier. Catalyst 1 has three obvious reduction signal peaks, and the corresponding central temperatures are 385°C, 415°C and 625°C, respectively. The main reduction peak moves to high temperature (625°C), which can be attributed to the formation of NiCo alloy. The formation of NiCo alloy can enhance the interaction with the carrier and increase the reduction temperature of Ni. A broad low-temperature peak is also observed in the temperature range of 250 to 350°C, which may be due to the partial reduction of a small amount of cobalt oxide phase. The reduction peak at 375 to 425°C comes from the reduction of the Ni component with weak interaction with the carrier.
[0076] Application Example 1
[0077] In this experiment, 3 mL of dimethyl maleate, 0.06 g of catalyst 1 screened at 30 mesh, and 27 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 1 MPa with pure hydrogen. The reaction temperature and pressure were set at 50°C and 1 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phase, and the gas phase component was only H2. After 30 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0078] Application Example 2
[0079] In this experiment, 10 mL of dimethyl maleate, 0.2 g of catalyst 2 screened at 20 mesh, and 70 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 2 MPa with pure hydrogen. The reaction temperature and pressure were set at 100 ° C and 2 MPa, and the stirring speed was 500 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phase, and the gas phase component was only H2. After 70 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0080] Application Example 3
[0081] In this experiment, 3 mL of dimethyl maleate, 0.06 g of catalyst 3 screened at 30 mesh, and 27 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 3 MPa with pure hydrogen. The reaction temperature and pressure were set at 150 ° C and 3 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phases, and the gas phase component was only H2. After 40 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0082] Application Example 4
[0083] In this experiment, 10 mL of dimethyl maleate, 0.2 g of catalyst 4 screened at 20 mesh, and 70 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 3 MPa with pure hydrogen. The reaction temperature and pressure were set at 150 ° C and 3 MPa, and the stirring speed was 500 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phases, and the gas phase component was only H2. After 75 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0084] Application Example 5
[0085] In this experiment, 3 mL of dimethyl maleate, 0.06 g of catalyst 5 screened at 30 mesh, and 27 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 4 MPa with pure hydrogen. The reaction temperature and pressure were set at 200 ° C and 4 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phases, and the gas phase component was only H2. After 60 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0086] Application Example 6
[0087] In this experiment, 5 mL of dimethyl maleate, 0.1 g of catalyst 6 screened at 30 mesh, and 45 mL of deionized water solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 4 MPa with pure hydrogen. The reaction temperature and pressure were set at 200 ° C and 4 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phase, and the gas phase component was only H2. After 30 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0088] Application Example 7
[0089] In this experiment, 10 mL of dimethyl maleate, 0.2 g of catalyst 7 screened at 60 mesh, and 70 mL of deionized water solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 4 MPa with pure hydrogen. The reaction temperature and pressure were set at 200 ° C and 4 MPa, and the stirring speed was 500 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phases, and the gas phase component was only H2. After 35 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0090] Application Example 8
[0091] In this experiment, 3 g of dimethyl maleate, 0.06 g of catalyst 8 screened at 30 mesh, and 27 mL of anhydrous methanol solvent were added to a 100 mL high-pressure intermittent hydrogenation reactor. After sealing, the reaction system was washed with N2 and H2 for 5 times, and then pressurized to 5 MPa with pure hydrogen. The reaction temperature and pressure were set at 250 ° C and 5 MPa, and the stirring speed was 600 r / min for continuous reaction. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was determined by hydrogen ion flame detector (FID) on HP-5 capillary column. TCD detected the content of each component in liquid and gas phases, and the gas phase component was only H2. After 60 minutes of reaction operation, the DMM conversion rate was 100% and the DMS selectivity was 100%.
[0092] Application Comparative Example 1
[0093] The catalyst application evaluation conditions were the same as those in Example 1. After the reaction was run for 80 min, the DMM conversion rate was 85% and the DMS selectivity was 95%.
[0094] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.
Claims
1. A Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst, characterized in that: The general formula of the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst is Ni-N-MO-Al2O3, wherein N represents one of Cr, Mn, Fe, Co or Cu, and MO represents one of Mg, Ca, Sr, Ba, Cd or Zn oxides; Al2O3 is used as a carrier, Ni, N and MO are metal active components, the carrier Al2O3 maintains a partial lamellar skeleton structure of the hydrotalcite at the nanoscale, and nanoparticles of the metal active components Ni and N and MO are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, Ni-N alloy nanoparticles and MO are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
2. The Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 1, characterized in that: In terms of mass percentage, the contents of the components in the Ni-N-MO-Al2O3 are as follows: Ni is 20-35%, N is 10-20%, MO is 8-35%, and Al2O3 is 35-55%.
3. The Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 2, characterized in that: The specific surface area of Ni-N-MO-Al2O3 is 145 to 180 m 2 ·g -1 The average pore size is 5-13 nm and the pore volume is 0.30-0.60 cm 3 ·g -1 , the Ni-N alloy particle size is 3.6~7.5nm.
4. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving nickel salt, N salt, M salt and aluminum salt in deionized water to prepare a metal salt solution; dissolving NaOH in deionized water to prepare a NaOH solution; dissolving Na2CO3 in deionized water to prepare a Na2CO3 solution; (2) dropping the metal salt solution and the NaOH solution into the Na2CO3 solution simultaneously for precipitation titration; (3) aging the precipitation solution after the precipitation is completed to obtain a precursor precipitate; (4) The precursor precipitate is washed, dried, and activated to obtain the catalyst Ni-N-MO-Al2O3.
5. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 4, characterized in that: In the step (1), the nickel salt, N salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, N salt, M salt and aluminum salt is 1-2:0.5-1:0.5-1:1, and the molar fraction ratio of the nickel salt + N salt + M salt and aluminum salt is 2-4:
1.
6. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 4, characterized in that: In the step (1), the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume is 75-250 mL; the concentration of the NaOH solution is 1-1.8 mol / L, and the volume is 150-200 mL; the concentration of the Na2CO3 solution is 0.3-0.6 mol / L, and the volume is 150-200 mL.
7. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 4, characterized in that: During the precipitation titration process in step (2), the volume flow ratio of the metal salt solution and the NaOH solution is controlled to be 0.75-2.5:1.5-2, the titration rate is 0.5-2.5 mL / min, the pH value of the mixed solution is maintained at 9-11, and the operating temperature is 50-100° C.; the aging temperature in step (3) is 20-30° C., and the aging time is 12-36 hours.
8. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 4, characterized in that: The washing liquid used in step (4) is deionized water, ethanol or a mixed solution of ethanol / water with a volume ratio of 3:1 to 1:3, and the number of washings is 3 to 5 times; the drying temperature is 70 to 200° C., and the drying time is 8 hours to 20 hours.
9. The method for preparing the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to claim 4, characterized in that: The activation treatment in step (4) includes: activation treatment 1: first calcining at 350°C to 600°C for 3h to 6h in a static air, flowing air, static nitrogen or flowing nitrogen atmosphere, with a heating rate of 2°C / min to 10°C / min; then reducing at 400°C to 600°C for 3h to 5h in a flowing hydrogen atmosphere or a hydrogen / nitrogen mixed gas atmosphere with a volume ratio of 1:0 to 3, with a heating rate of 2°C / min to 10°C / min; or activation treatment 2: directly reducing at 400°C to 600°C for 3h to 5h in a flowing hydrogen atmosphere or a hydrogen / nitrogen mixed gas atmosphere with a volume ratio of 1:0 to 3, with a heating rate of 2°C / min to 10°C / min.
10. The use of the Ni-based "bimetallic-base-acid" multifunctional hydrotalcite catalyst according to any one of claims 1 to 3, characterized in that: Used for semi-hydrogenation of dimethyl maleate to produce dimethyl succinate.
Citation Information
Patent Citations
Dimethyl maleate hydrogenating catalyst and preparation method thereof
CN103657693A
Cited By
Non-silicon-based porous adsorption catalytic coupling material and preparation method thereof
CN122377414A
A non-silicon-based porous adsorption and catalysis coupling material and a preparation method thereof
CN122377414B